PENGARUH MEDIA FILM DOKUMENTER TERHADAP KETERAMPILAN MENULIS SISWA PADA MATERI TEKS EKSPLANASI KELAS V SD - Nurul Fadilah; Ida Sulistyawati; Pana Pramulia (Lembaga Pengembangan Kinerja Dosen, 2022)
The context of this research is that writing skills are very important for learning, because they can train students to think, channel their desires, emotions, and express their ideas.. The use of documentary film media tells true stories about natural events in accordance with explanatory text material that tells about natural or social phenomena that can occur, such as about water, plastic which is the source of human life. The objective of this research, the researcher wants to know is there any effect of documentary film media on the writing skill of the fifth grade students of Sedatigede II Elementary School. While the research methodology used is quantitative by using a Quasi-Experimental design in the form of Nonequivalent Control Group Design. The research subjects were class V A as the experimental class and class V C as the control class at SDN Sedatigede II Sidoarjo with a total of 35 students. The data collection method used is an assessment in the form of a performance test with the task of writing an explanatory text. Using statistical analysis methods, the formulas used are normality test, homogeneity test and T-test. The test before and after using the media with the SPSS version 22 application were used. The results of this study were based on the results of the independent sample test data analysis, which showed the value of sig < 0.05, namely sig. (2-tailed) of 0.000. From these results, it was concluded that there was an effect of documentary film media on students' writing skills in the explanatory text material of fifth grade students of Sedatigede II Elementary School. This is reinforced by the significant difference in skill test scores in the experimental and control groups before and after treatment.